The interpersonal effects of emotional tears on person perception and intention to provide support - Martins, Diogo Barros (2021)
Emotional crying seems to have a communicative function, and observers tend to respond with help to tearful faces. This study arises from the importance of analyzing the social impact of the tear. It investigates to what extent the presence of tears affects the judgment of the target person (perception of traits such as warmth and competence) and the intention to help, adding potential moderating variables, such as the gender of the perceiver, the attributes of the target (sex), and the context (e.g., valence and social). A sample of 156 participants (96 females, 56 males, four of whom did not answer this question), were exposed to four images of people's faces (which varied in gender), accompanied by a brief description of the situation. In half of these cases, the faces showed tears, added digitally. Participants were asked to report their perception of the target's attributes (warmth and competence) and their intention to help. The results showed the effect of the presence of tears in all the dependent variables. Participants expressed a higher intention of helping a target with tears than targets no showing tears. There was also an effect of the valence of the situation in the intention of support, suggesting a greater intention of support a target in positive and negative situations than in neutral situations. It was found that targets that had tears were perceived as warmer and less competent, although this effect was depended on the valence of the context. This study is in line with previous research that highlight the social importance of tears.